A operacionalização da política de atenção à Pessoa com Deficiência: uma análise orientada pela promoção, defesa e garantia de direitos - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The discussion on topics involving "persons with disabilities" is complex and challenging for reasons ranging from segregation and exclusion - historically experienced by people with disabilities - to own understanding and definition of the most appropriate term for the population segment. Another aspect that makes the challenging theme and complex refers to the percentage of 32% of the population and 23% of Amazonians who declared with a disability in the Census of 2010, which brings up some questions and reflections, among which: how government has organized to meet the demands of people with disabilities. Among broad aspects to be addressed on the theme "people with disabilities", defined as general objective of this research, analyze the implementation of the State Care of Persons with Disabilities of coordinated Amazonas Policy by the Secretary of State for the Rights of Persons with Disabilities and specific objectives: to name the projects developed by SEPED, relating them to the guidelines of State Policy for Attention to People with Disabilities; Verify how effective the intersectionality between the state departments for implementation of the policy directed to persons with disabilities; Knowing the design of the managers of the State Policy on Care for Persons with Disabilities about the challenges and possibilities for its operation; and identify the vision of the person with disabilities with regard to changes in your life, from its inclusion in the actions developed by SEPED. Was adopted qualitative and quantitative approaches, favoring a qualitative nature, depending on the size of the meanings that respondents attach to the history, facts, people and objects that surround your social universe. In the field research were applied two types of forms of semi-structured interviews, one for managers and one for users of politics. Among the results of the research, the result of discussions and analyzes presented in the four chapters of the thesis, it is argued that there are specific actions for people with disabilities, segment achievements of fruit in the area of legally established rights, among the achievements are: the creating laws, specific programs and projects, such as the Brazilian Law of Inclusion, the no limit Living program, the attention of State Policy for Persons with Disabilities and its own Secretariat which serves exclusively the public concerned. However, we found that there are still many challenges put to SEPED in the implementation of the state policy process, among the challenges are: a) to fully meeting the needs of people with disabilities, as set out in the political attention axes; b) expansion and strengthening of social control popular participation, in order to ensure the provision of public policy as a citizen's right and duty of the State; c) break with the culture of Rancid "please" and "help" so that public policies start to be intentionally offered as a legal and social rights of citizens. It is concluded that the SEPED has advanced in providing services for people with disabilities, but it needs an institutional reorganization, so that coordination of actions has focused on creating intersectoral assistance strategies in order to ensure full attention to the demands of the public it serves.
Keywords: Pessoa com Deficiência; Política Pública; Intersetorialidade; Controle Social; CIÊNCIAS HUMANAS: SERVIÇO SOCIAL